1986
DOI: 10.2337/diab.35.11.1233
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic AMP Phosphodiesterase in Diabetes: Effect of Glyburide

Abstract: Low-Michaelis constant cAMP phosphodiesterase (PDE; EC3.1.4.C) activity is inhibited in tissues of rats with type I ketosis-prone diabetes and is restored to normal by insulin treatment. To determine whether the oral hypoglycemic agent glyburide affected tissue cAMP PDE activity in non-insulin-dependent oral agent-treatable diabetes, cAMP PDE activity was measured in the liver and fat of animals rendered diabetic by low-dose streptozocin (STZ-DM) and treated for 3 wk with oral glyburide (360 micrograms/kg). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 4 publications
2
5
0
Order By: Relevance
“…These defects were normalized after treatment of the rats with pioglitazone, results which are in agreement with early studies in diabetic patients (26), showing that reduced PDE activity in adipocytes is normalized after treatment with insulin or oral antidiabetic agents (26). Consistent with these studies, our data demonstrate that troglitazone can block the ability of ceramide to stimulate lipolysis and induce downregulation of PDE3B in 3T3-L1 adipocytes.…”
Section: Discussionsupporting
confidence: 93%
“…These defects were normalized after treatment of the rats with pioglitazone, results which are in agreement with early studies in diabetic patients (26), showing that reduced PDE activity in adipocytes is normalized after treatment with insulin or oral antidiabetic agents (26). Consistent with these studies, our data demonstrate that troglitazone can block the ability of ceramide to stimulate lipolysis and induce downregulation of PDE3B in 3T3-L1 adipocytes.…”
Section: Discussionsupporting
confidence: 93%
“…In parallel with reduced cytosolic cAMP levels, the drugs stimulate the activity of the microsomal low Km cAMP-specific PDE in rat adipocytes within the same concentration range. This corroborates previous reports concerning sulphonylurea action on PDE activity [65,66]. At present it is not known whether a sulphonylureainduced inhibition of adenylate cyclase, as reported for rat heart and liver [67], supports the decline of cAMP levels.…”
Section: Discussionsupporting
confidence: 80%
“…Stimulation of the phosphodiesterase activity by insulin may contribute in part to this insulin effect (19,20). In diabetic rats administered a low dose of streptozocin, the activity of phosphodiesterase was reduced in the liver and fat tissues, and this enzyme activity was restored almost 1/ATP, to normal by glyburide treatment (24). It was reported that tolbutamide increased the level of cAMP by stimulating adenylate cyclase activity (21) and by inhibiting cAMP phosphodiesterase activity (22).…”
Section: Discussionmentioning
confidence: 99%